Out of the ordinary : finding hidden threats by analyzing unusual behavior - Hollywood, John S., 1973-; Rand Corporation (Santa Monica, Calif. : RAND Corp., 2004)
Presents a unique appraoch to selecting and assembling disparate pieces of information to produce a general understanding of a threat. The Atypical Signal Analysis and Processing schema identifies atypical behavior potentially related to terror actvity; puts it into context; generates and tests hypotheses; and focuses analysts' attention on the most significant findings. A supporting conceptual architecture and specific techniques for identifying and analyzing out-of-the-ordinary information are also described.
Introduction -- Data analyzed in the ASAP Schema -- The Atypical Signal Analysis and Processing Architecture -- Finding the dots -- Connecting the dots -- Understanding the dots: generating and testing hypotheses -- Conclusion -- Case study: "The November 9th incident" -- Systems realted to the ASAP architecture.
"MG-126-RC."
Includes bibliographical references (pages 151-155) and appendices.
Title from title screen (viewed 11/23/2004).
eBooks on EBSCOhost
Keywords: Criminal behavior, Prediction of -- United States; Crime forecasting -- United States; Criminal methods -- United States; Terrorism -- Forecasting; Terrorism -- Psychological aspects; Intelligence service -- United States; National security -- United States; Criminalité -- Prévision -- États-Unis.; Modus operandi (Criminologie) -- États-Unis.; Terrorisme -- Prévision.; Terrorisme -- Aspect psychologique; POLITICAL SCIENCE -- Political Freedom & Security -- Law Enforcement; POLITICAL SCIENCE -- Security (National & International); Crime forecasting; Criminal behavior, Prediction of; Criminal methods; Intelligence service; National security; Terrorism -- Forecasting; Terrorism -- Psychological aspects; United States